2022
DOI: 10.3390/jcm11040902
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of MMP-8 and MMP-9 as Markers in Chronic Subdural Hematoma

Abstract: Chronic subdural hematoma (CSDH) is a common neurological disease that involves the collection of blood products in the subdural space. The progression of CSDH is an angiogenic and inflammatory process, but the multifactorial mechanisms underlying CSDH are still not fully understood. We aimed to identify one or more factors that may play an important role in the development of CSDH. We enrolled 83 patients with CSDH, including 17 postoperative patients, and analyzed 20 markers in the hematoma fluid and periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The concentrations of MMP-8 and MMP-9 in the control (normal) group are shown in Table 4 (p < 0.01). Based on our previous study ( 11 ), the concentration of MMP-8 was significantly higher in the normal group compared to that in both preoperative and postoperative CSDH groups, while that of MMP-9 was significantly lower. All CSDH membranes were immunostained for MMP-8 and MMP-9 in all samples.…”
Section: Resultsmentioning
confidence: 72%
See 4 more Smart Citations
“…The concentrations of MMP-8 and MMP-9 in the control (normal) group are shown in Table 4 (p < 0.01). Based on our previous study ( 11 ), the concentration of MMP-8 was significantly higher in the normal group compared to that in both preoperative and postoperative CSDH groups, while that of MMP-9 was significantly lower. All CSDH membranes were immunostained for MMP-8 and MMP-9 in all samples.…”
Section: Resultsmentioning
confidence: 72%
“…Based on our previous study, MMP-8 and MMP-9 may contribute to CSDH pathogenesis in different ways ( 11 ). We found that the MMP-8 concentration was significantly higher in the normal group compared to that in preoperative and postoperative groups, whereas the MMP-9 concentration was significantly lower.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations